Strategi Strategi Komunikasi Pendidikan untuk Meningkatkan Kualitas Pendidikan di Era Gen Z - Chairunisa, Hera; Sahara, Siti; Karimah, Maulidea; Lubis, Winny Meilita; Gultom, Deviany Valeria; Limayasi, Chaterine Nimas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study discusses educational communication strategies to improve the quality of education in the Generation Z era, which requires a communication approach that suits the unique characteristics influenced by technology. Using a qualitative approach and literature analysis, the research aims to identify effective educational communication strategies for Generation Z. Key findings include visual preferences, personalization, interactivity, problem-based learning, immersive technology, digital mentoring, flexibility, and social responsibility. Recommended strategies include visual content, adaptive learning, online discussions, VR/AR, digital mentoring, mobile learning, social projects, gamification, and multi-platform communication. It is important to understand the characteristics of Generation Z and adapt in relevant and effective ways, as well as create education that is technologically advanced and of great value. Implementation suggestions include digital teacher training, online cultural diplomacy, and educational media policies. This research provides valuable guidance for the development of educational strategies that suit the needs of Z Generation.